Needs and Resources: Understanding the Complex Interplay for Sustainable Development ("Conference on Universal Science Research 2023", 2023)
This scientific article explores the intricate relationship between human needs and available resources, with a particular focus on the context of sustainable development. The fulfillment of basic human needs while ensuring the responsible management of natural resources is a critical challenge facing societies worldwide. This article delves into the various dimensions of needs and resources, their interdependence, and the implications for sustainable development. It examines the role of technological advancements, policy interventions, and societal behaviors in optimizing the balance between needs and resources to ensure a prosperous and equitable future.